Determination of Isomaltooligosaccharides in Milk Powder by Ultra-High Performance Liquid Chromatography–Tandem Mass Spectrometry. (3rd March 2016) - Jiao, Yanni; Li, Fenghua; Jiang, Dafeng; Li, Wei; Chen, Jindong
ABSTRACT: Isomaltooligosaccharides are widely used in food with health benefits. A sensitive and selective method for the determination of three isomaltooligosaccharides is reported using ultra-high performance liquid chromatography–tandem mass spectrometry. The method was validated by characterization of the linearity, accuracy, precision, and the limits of detection and quantification. Under the optimized conditions, the calibration relationships were linear for the analytes with correlation coefficients exceeding 0.998. The recoveries were from 91.5% to 107.6% with coefficients of variation below 9.0%. The limits of detection and quantification were 1.20 µg mL −1 and 3.60 µg mL −1 for isomaltose, 0.15 µg mL −1 and 0.50 µg mL −1 for panose, and 0.55 µg mL −1 and 1.80 µg mL −1 for isomaltotriose. The validated method was employed for the determination of isomaltooligosaccharides in milk powder.